Pusat Pelatihan Kerajinan Tangan Dan Kuliner Di Kampar Dengan Pendekatan Arsitektur Organik - Devi Endriani; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Design of Craft and Culinary Creation Training Center is intended fulfillmentof self-development activities. This design purpose to accommodate and promote handicrafts and culinary typical of the region as a whole and become more independent. Various handicrafts can be promoted outside Kampar District to be known. This approach design uses of Organic Architecture. The approaches are applied partially or completely to the building. Organic architecture takes care of the environment and harmony with the tread. This approach is in accordance with the Training Center for Crafts and Culinary Manufacture which should be close to nature. The materials used for handicrafts and culinary are also materials that come from nature. Nature Building and Of the People are two of the seven basic concepts of Organic Architecture design. Merging the two led to the concept of Nature Building for The People. The Hyacinth flower is a plant that becomes a prominent thing on the site. The shape and several traits of this flower become inspiration in the design of Craft and Culinary Training Center.The floating Hyacinth flower became the inspiration of the floating building design. While the amount of six strands of flower petals transformed into six building masses plus a mass of buildings in the middle as the center. Keywords: Training, Crafts, Culinary, Organic Architecture